Strategies to minimize SARS-CoV-2 transmission in classroom settings: combined impacts of ventilation and mask effective filtration efficiency. (13th September 2021) - Rothamer, David A.; Sanders, Scott; Reindl, Douglas; Bertram, Timothy H.
Abstract: Strong evidence exists indicating that aerosol transmission of the novel coronavirus SARS-CoV-2 is a significant transmission modality. We experimentally evaluated the impact of ventilation on aerosol dynamics and distribution along with the effective filtration efficiency (EFE) of four different mask types, with and without mask fitters, in a classroom setting. These were used to estimate aerosol conditional infection probability using the Wells–Riley model for three scenarios with different ventilation and mask interventions. Aerosol measurements confirmed that aerosol in the room was uniform within a factor of 2 for distances >2 m from the source. Mask EFE results demonstrate that most masks fit poorly with estimated leakage rates typically >50%. However, EFEs approaching the mask material FE were achievable using mask fitters. Infection probability estimates indicate that ventilation alone is not able to achieve probabilities <0.01 (1%). The use of moderate to high EFE masks reduces infection probability, >5× in some cases. Reductions provided by ventilation and masks are synergistic and multiplicative. The results reinforce the use of properly donned masks to achieve reduced aerosol transmission of SARS-CoV-2 and other infectious diseases and motivate improvements in the EFE of masks through improved design or use of mask fitters.